Psychological empowerment as a mediating effect on the relationship between work stress, pay satisfaction and organizational commitment among academic staff - Farah Lina, Azizan (2014)
Malaysia needs work forces that possess high commitment, productivity and progressiveness, competitive, and efficient in its mission to achieve the Vision 2020 targets. The aim of this study is to investigate the mediating effect of psychological empowerment on the relationship between work stress, pay satisfaction and organizational commitment among academic staff in public universities. This study is focus on academic staffs from public universities in Northern Malaysia. Academic staffs were chosen because they are dealing with a lot of tasks. A total number of 400 academics were chosen as respondents for the study but only 297 academics responded to the questionnaire. Statistical Package software for Social Science (SPSS) Version 19.0 was used to analyze the collected data. Factor analysis, multiple regressions and correlation were applied to this study. The Pearson correlation analysis indicated that work stress is a negatively associated with organizational commitment and psychological empowerment whereas pay satisfaction, psychological empowerment and organizational commitment have positive relationship by each other. Furthermore, the multiple regression analysis revealed that psychological empowerment has a partially mediate on the connection with work stress, pay satisfaction and organizational commitment. It is suggested for future research to look at the way to influence and shaping the attitudes of academic staff by investigate some other important factors that able to improve their commitment towards organization